PENGARUH DOSIS PUPUK KANDANG KELINCI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU (Brassica juncea L) - Maria Diana Dimun; Putu Lasmi Yulianti Sapanca; Ni Putu Eka Pratiwi; Listihani; Luh Putu Yuni Widyastuti (Agrofarm: Jurnal Agroteknologi, 2023)
This study aims to determine the effect of providing rabbit manure on the growth and yield of mustard greens., starting from March 10 to April 10, 2021, at Kebun Kalpataru Denpasar Selatan. This study used a randomized block design (RAK) with 6 treatments and 4 replications. The treatment of kandang kelinci D0(without rabbit manure), fertilizer consisted of D1 (25g/5 kg soil), D2 (50g/5 kg soil), D3 (75g/5 kg soil), D4 (100g/5 kg soil) D5 (125g /5 kg of soil). Each treatment was repeated 4 times so that the total number of treatments became 24. The results showed that the treatment of 50 grams of rabbit manure (D2) gave the best growth and yield compared to other treatments of rabbit manure for all observation parameters such as plant height, number of leaves, leaf area, fresh weight of plants, total dry weight of plants, fresh weight without plant roots, dry weight without plant roots.